Analysis of the use of GPS/GLONASS data for dif ferent satellite positioning methods considering the influence of the Brazilian ionospheric conditions - Jerez, Gabriel Oliveira [UNESP]; Alves, Daniele Barroca Marra [UNESP] (Instituto Panamericano de Geografia e Historia, 2022)
GLONASS (GLObal NAvigation Satellite System) and GPS (Global Positioning System) are the pioneer satellite navigation systems. The combined use of GPS and GLONASS data initially aroused interest, but research investigating both signals declined greatly in the late nineties due to the fast degradation that GLONASS suffered. However, after a plan to re-establish the system, in 2011 GLONASS returned to a complete constellation and global coverage. In addition to the reestablishment, the system also went through a modernization process, with new generations of satellites being developed, refinements of the time and reference systems and new control stations being installed. Besides the use of combined data, other factors that influence the positioning quality are the methods employed and the errors to which the transmitted signals are subject. Regarding errors, the ionosphere is an important source, especially for users of simple frequency receivers. Considering this scenario, the present work aimed to conduct a study of the GLONASS system, as well as to analyze the improvements presented in the positioning using its data combined with GPS data in different positioning methods, considering different ionospheric conditions. In general, it was possible to verify the viability of using GLONASS data combined with GPS in all the positioning methods evaluated. In general, it was possible to verify the viability of using GLONASS data combined with GPS in all the positioning methods evaluated, with improvement in more than 97% of the cases analyzed for point positioning and around 70% of the cases with relative positioning.
Análise do uso de dados GPS/GLONASS em diferentes métodos de posicionamento por satélites considerando a influência das condições ionosféricas brasileiras
Keywords: GPS/GLONASS; Ionosphere; Positioning; PPP; VRS